The Relationship Between Adolescents' Knowledge About the Dangers of Drugs and Health Behavior - Roza, Amelia; Sinaga, Rosa (Cattleya Darmaya Fortuna, 2022)
This study investigates the relationship between adolescent knowledge of drug dangers and health behavior at SMA Negeri 1 Panyabungan Selatan, Mandailing Natal Regency. Narcotics, whether plant-based, synthetic, or semi-synthetic, are often associated with addiction and dependence. The abuse and illicit trafficking of drugs have severe consequences, including damage to individuals, communities, and the nation's future. Approximately 200 individuals were suspected of involvement in drug-related activities, prompting a community-oriented approach to address the issue. Using a descriptive research design, this study employed a questionnaire as the research instrument and utilized accidental sampling to select 36 respondents from class XI Science students in 2022. Univariate analysis, conducted using the SPSS program, revealed varying levels of knowledge among respondents: 20 individuals (55.6%) exhibited good knowledge, 6 individuals (16.7%) had sufficient knowledge, and 10 individuals (27.8%) possessed poor knowledge regarding drug dangers. This study sheds light on the importance of understanding the relationship between adolescent knowledge of drug dangers and their health behavior, offering insights for interventions aimed at promoting informed decision-making and healthy lifestyles among youth.